Volume 04, 1966 Trial Transcript (Retrial of Samuel H. Sheppard): Testimony; State Rests; Motions for Directed Verdict and Time - Cuyahoga County Court of Common Pleas (1966)
Trial transcripts, pages 597-1165, covering November 5, 1966 morning session through November 10, 1966 morning session Includes testimony of prosecution witnesses Patrick Gareau, Cleveland homicide detective; Samuel Gerber, Cuyahoga County Coroner; Michael S. Grabowski, Cleveland Police Dept. fingerprint unit; Jerome Poelking and Henry Dombrowski, Cleveland Police Department scientific investigation unit; Mary Cowan, medical technologist, Cuyahoga County Coroner's Office; the state rests; motions for directed verdict; defense witnesses Jack Krakan, deliveryman to the Sheppards; Paul L. Kirk, professor of criminalisticshttps://engagedscholarship.csuohio.edu/sheppard_transcripts_1966/1003/thumbnail.jp